2005
DOI: 10.1021/jo051973q
|View full text |Cite
|
Sign up to set email alerts
|

On the Origin of Cis/Trans Stereoselectivity in Intramolecular Diels−Alder Reactions of Substituted Pentadienyl Acrylates: A Comprehensive Density Functional Study

Abstract: [structures: see text] A gas-phase B3LYP/6-31+G(d) study of substituent effects on the stereochemistry of both intramolecular Diels-Alder (IMDA) reactions of 9-E- and 9-Z-substituted pentadienyl acrylates and intermolecular Diels-Alder (DA) reactions between butadiene and monosubstituted alkenes and 3-substituted acrylates is reported and involves the calculation of 230 transition structures. It was found that, although exo ("anti-Alder") addition of monosubstituted ethenes to butadiene is the norm, Alder endo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
20
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 24 publications
(21 citation statements)
references
References 31 publications
1
20
0
Order By: Relevance
“…The transition‐state geometry and weak preference for cis over trans diastereoselectivity for products illustrated in Figure 1 is consistent with the trends observed for similarly substituted pentadienyl acrylate IMDA cycloadditions 7a. Overall, the transition states display varying degrees of asynchronicity with advanced internal bond formation.…”
Section: Resultssupporting
confidence: 80%
See 1 more Smart Citation
“…The transition‐state geometry and weak preference for cis over trans diastereoselectivity for products illustrated in Figure 1 is consistent with the trends observed for similarly substituted pentadienyl acrylate IMDA cycloadditions 7a. Overall, the transition states display varying degrees of asynchronicity with advanced internal bond formation.…”
Section: Resultssupporting
confidence: 80%
“…The exo transition states are geometrically less able to meet these requirements, and consequently one observes a higher degree of asynchronicity, whereby the exo transition states are geometrically distorted to achieve the lowest‐energy configuration. Asynchronicity can be defined by four parameters: bond‐forming asynchronicity (Δ R as = | R pr – R in |, where R pr and R in are the lengths of newly forming peripheral and internal sp 3 bonds),7a and the magnitude of the two endocyclic dihedral angles about the two newly forming carbon bridgeheads, θ dh5 = O5–C4–C8–C7 and θ dh6 = C3–C4–C8–C9 (Table 2). The torsional angle θ as = C1–C4–C8–C9 is defined by Houk et al18 as twist‐mode asynchronicity and is recognised as an important parameter in defining asynchronous IMDA cycloadditions 7.…”
Section: Resultsmentioning
confidence: 99%
“…We previously noted this trend in a broad scope DFT (B3LYP) study (see Introduction). 41 This observation of enhanced endo-stereoselectivity with a smaller HOMO diene -LUMO dienophile energy gap is suggestive of SOIs, although this correlation does not constitute evidence of causation.…”
Section: Computational Methodologymentioning
confidence: 99%
“…As part of a DFT (B3LYP) study of intramolecular Diels-Alder reactions, we investigated substituent effects on endo/exo selectivities of Diels-Alder reactions between BD and monosubstituted ethylenic dienophiles (CH 2 ]CH-Z; Z ¼ CN, CO 2 Me, CO 2 H, NO 2 , CHO, COMe). 41 It was found that endo selectivity is predicted for methyl vinyl ketone and acrolein. However, this nding, like those from earlier studies that used the Hartree-Fock procedure, 38,39 is unreliable because B3LYP seriously underestimates dispersion energies, thereby skewing the selectivity towards the exo reaction channel.…”
Section: Introductionmentioning
confidence: 99%
“…We postulate that this factor is a stabilizing interaction between the diene and the tether carbonyl group, which occupies an endo disposition with respect to the diene moiety. This stabilizing interaction could arise either from secondary orbital interactions,13, 37 perhaps of the Singleton [4+3] kind,38 between C4 and C7, or from electrostatic interactions between the dipole and quadrupole moments of the diene and carbonyl groups,39 or from a combination of both types of interaction. [40 , 41] Our calculations on the IMDA TSs for 3 – 9 , in which the composition of the tether is varied, support this postulate, as will now be discussed.…”
Section: Resultsmentioning
confidence: 99%